Studies of spore/pollen wall ultrastructure in fossil and living plants: A review of the subject area and the contribution of Bernard Lugardon - Wellman, C.H.; Grauvogel Stamm, L.; Guignard, G.
Studies of land plant spores/pollen include a large subject area of both living and fossil material. They impact on many areas of science, ranging from classical neobotany and palaeobotany, analysis of present and past environments and climate change, geological correlation of rocks, agronomy, medicine (allergy studies)and so forth. Advances in the scientific understanding of spores/pollen have to a large extent been driven by technical advances in microscopy (essentially the medium through which one observes these microscopic reproductive particles). One of the major technological advances that has impacted spore/pollen research was the development in the 1950s of commercially available transmission electron microscopy (TEM). This instrumentation enabled for the first time high powered magnification of sections of spores/pollen. This paved the way for the description of cellular features in extant spores/pollen, which made it possible to engage in studies of ontogeny (including exospore/exine development). The latter proved especially useful for taxonomic and phylogenetic analysis, especially as it can often be extended back into the rich spore/ pollen fossil record. This paper provides a brief review of the historical development of spore/pollen research, and places in context the influence of Bernard Lugardon (1930-2007), one of the pioneers of TEM analysis of spores/pollen. Sadly Bernard passed away on the 26th January 2007. The papers collected in this special volume are dedicated to the memory of Bernard Lugardon.
Keywords: SPORES; POLLEN; ULTRASTRUCTURE; TRANSMISSION ELECTRON MICROSCOPY; BERNARD LUGARDON